Introduction - Hamlaoui, Fatima (ZAS Papers in Linguistics, 2014)
Bantu languages have been at the heart of the research on the interaction between syntax, prosody and information structure. In these predominantly SVO languages, considerable attention has been devoted to postverbal phenomena. By addressing issues related to Subjects, Topics and Object-Verb word orders, the goal of the present papers is to deepen our understanding of the interaction of different grammatical components (syntax, phonology, semantics/pragmatics) both in individual languages and across the Bantu family. Each paper makes a valuable contribution to ongoing discussions on the preverbal domain.